FIRST REPORT ON THE ANTI-UROLITHIATIC ACTIVITY OF VIBURNUM OPULUS ON UROLITHIASIS/CRYSTALLURIA IN DOGS AND CATS - Umit Ozcan; Gülcin Saltan Iscan; Emre Kulluk; Basar Ulas Sayilkan; Cagatay Esin; Zeynep Nurselin Çolak; Yucel Meral; Duygu Dalgin (Journal of Animal and Plant Sciences, 2023)
Lower urinary tract problems were increasingly encountered in small animal practice. Urinary stones and crystals are common problems in these cases and are still a problem in cats and dogs. Dilution of urine or restriction of mineral intake is a way to reduce urolithiasis/crystalluria. Viburnum Opulus was prescribed as anti-urolitiatic in human medicine. The objective of this study was to evaluate the efficacy of Viburnum Opulus in urolithiasis or crystalluria in companion animals. For this purpose, 42 animals were presented with urinary system problems and diagnosed with urolithiasis or crystalluria, which were included in the study and divided into two main groups (21 calcium oxalate, 21 struvite) and two subgroups (Control and Study). The urinary score was noted as the presence of pollakiuria, crystals in the microscopic examination, hematuria, stranguria, proteinuria, leucocytes, and blood in the urine. The mean ages were 3.81 and 3.95 for the calcium oxalate and struvite groups, respectively. It was determined that the clinical urinary score of the calcium oxalate control group was 11.39 before the treatment and increased to 14.06 at the end of 2 weeks. However, it was observed that this score decreased from 10.71 to 8.71 in the calcium oxalate study group. In calcium oxalate-diagnosed animals, a decrease in clinical scores was significant in the Viburnum opulus group than in controls. The urinary scores decreased in both struvite subgroups, but no statistical differences were determined. All animals except the calcium oxalate control group were clinically healthy at the second visit. Using Viburnum opulus as an integrative medical approach will provide safe and effective treatment for urolithiasis/crystalluria.
Keywords: viburnum opulus; urolithiasis; crystalluria; small animal; supplement